Association Between ABCA1 Gene Polymorphisms and the Risk of Hypertension in the Chinese Han Population - Ren, Yanli; Tong, Enyu; Di, Chunhong; Zhang, Yunheng; Xu, Liangwen; Tan, Xiaohua; Yang, Lei (Frontiers in Public Health, 2022)
Background Hypertension is rising as a major public health burden around the world. This study explored the association between single-nucleotide polymorphisms (SNPs) in the adenosine triphosphate (ATP)-Binding Cassette Subfamily A1 (ABCA1) gene and hypertension among Chinese Han adults. Method A total of 2,296 Han Chinese in southeast China were recruited for this study. We collected medical reports, lifestyle details, and blood samples from individuals. The polymerase chain reaction-ligase detection reaction (PCR-LDR) method was used to detect the genotypes of these SNPs in the ABCA1 gene. Results After adjusting some covariates, the additive and recessive models of the rs2472510 and rs2515614 were significantly associated with hypertension. The haplotypes TCTA (rs2297406-rs2472433-rs2472510-rs2515614) were associated with high SBP, and the haplotypes CCTA, TCTA, and TTTA were associated with high diastolic blood pressure (DBP). Conclusion The results of the relationship between the polymorphisms of rs2297406, rs2472433, rs2472510, and rs2515614 in ABCA1 and hypertension in southeastern China would provide a theoretical basis for genetic screening and disease prevention.